Those Who Remain : a Photographer's Memoir of South Carolina Indians - Crediford, Gene J. (Contemporary American Indian studies., 2011)
When DeSoto (in 1540) and later Juan Pardo (in 1567) marched through what was known as the province of Cofitachequi (which covered the southern part of today's North Carolina and most of South Carolina), the native population was estimated at well over 18,000. Most shared a common Catawba language, enabling this confederation of tribes to practice advanced political and social methods, cooperate and support each other, and meet their common enemy. The footprint of the Cofitachequi is the footprint of this book. The contemporary Catawba, Midland, Santee, N.